ANALISIS WALKABILITY PADA KAWASAN STASIUN MANGGARAI MENUJU HALTE TRANSJAKARTA MANGGARAI - Iswara, Khalisa Gina; Adwitiya, R. Ivan; Sumabrata, R. Jachrizal; Kusuma, Andyka (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2023)
Walkability refers to the ease of walking in an area, considering factors like safety, comfort, and security due to the presence of interconnected pathways. In this study, an assessment of walkability was conducted from Manggarai Station to the Manggarai TransJakarta Bus Stop to evaluate the quality of the infrastructure for pedestrian. Data was collected through both on-site observations and the distribution of online through social meadia. Findings from the observations indicate that the walkability score for the path from Manggarai Station to the Manggarai TransJakarta Bus Stop is 68.5, categorizing as